Analisis Perbandingan Keamanan Data Dan Privasi Pengguna Aplikasi Telemedisin Berdasarkan Hukum Indonesia: Halodoc Dan Alodokter (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
This research was conducted to obtain information regarding data security and privacy of users of digital health applications, Halodoc and Alodokter, based on legal regulations in Indonesia. The method used is a qualitative method through sources such as literature reviews, journals, scientific works and other media, as well as a quantitative method through calculating the level of conformity of regulations on applications with applicable laws and regulations. The results obtained in both applications are that data security and user privacy are met by seven out of ten indicators, and both make their best efforts to protect and secure their users' personal data, however there is no guarantee that the platform will be safe and reliable.